Dynamic performance analysis and quantitative evaluation for ultraprecision aerostatic spindle. (January 2020) - Wei, Ruocheng; An, Chenhui; Wang, Zhenzhong; Xu, Qiao; Lei, Xiangyang; Zhang, Jianfeng
For optics used in high-power laser beams, high accuracy requirements in full spatial frequency must be fulfilled. Among them, the allowable root mean square value is less than 5 nm in the PSD1 band. In order to evaluate the dynamic performance of the spindle system and put forward a quantitative index, a novel accurate model of the spindle system was built and a series of dynamic simulations were performed. Harmonic response analysis reveals natural frequencies and frequency response functions. Transient analysis indicates vibration waveforms of the tool-tip. Furthermore, by analyzing surface topography, it can be found that the medium-frequency waviness in the machined surface matches the vibration waveform. Obviously, the medium-frequency waviness is generated by the modal vibration of the spindle system. So that a quantitative index for the aerostatic spindle is proposed: when the amplitude of vibration in transient analysis is smaller than 8 nm, the allowable error in the PSD1 band can be fulfilled.